MAC OS 9.1 - Langer, Maria (Visual quickstart guide., 2001)
Want to really learn how to use your Mac? Here's your chance, because Mac OS 9.1: Visual QuickStart Guide gives you everything you need to get straight to work managing your files, navigating menus, working with utilities and applications, customizing your system, finding your way on the Internet and sharing your files over a network. Like all Visual QuickStart Guides, this book is packed with step-by-step instructions, illustrations and loads of tips. Beginners can follow it as a tutorial, while current Mac users can use it to get up to speed with the latest OS release.